2009
DOI: 10.1063/1.3126521
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal magnetic force microscopy: Separation of short and long range forces

Abstract: An application of bimodal atomic force microscopy [T. R. Rodriguez and R. Garcia, Appl. Phys. Lett. 84, 449 (2004)] which allows simultaneous and separated imaging of both long range magnetic and shorter range topographical forces is described. This technique has a spatial resolution and a signal-to-noise ratio at least as good as other magnetic force microscopy techniques with the advantage of requiring only a single pass. Besides being an improvement on existing magnetic imaging techniques, the results also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 16 publications
0
49
0
Order By: Relevance
“…the fundamental mode and a higher order mode, allows for a simultaneous tracing of both the topography using the interaction response on one mode and compositional information contained in the higher order mode response [9,10]. Transferred to magnetic force microscopy (MFM), a descendant of dSFM, such an approach based on the excitation of two flexural eigenmodes enables a parallel measurement of the sample topography and the long range magnetostatic interactions of the ferromagnetic tip with the sample stray field [11][12][13]. By this means some disadvantages of the widely used twopass MFM technique can be avoided.…”
Section: Multi-frequency Dsfmmentioning
confidence: 99%
“…the fundamental mode and a higher order mode, allows for a simultaneous tracing of both the topography using the interaction response on one mode and compositional information contained in the higher order mode response [9,10]. Transferred to magnetic force microscopy (MFM), a descendant of dSFM, such an approach based on the excitation of two flexural eigenmodes enables a parallel measurement of the sample topography and the long range magnetostatic interactions of the ferromagnetic tip with the sample stray field [11][12][13]. By this means some disadvantages of the widely used twopass MFM technique can be avoided.…”
Section: Multi-frequency Dsfmmentioning
confidence: 99%
“…However, the use of the intermittent contact mode in vacuum remains challenging. 2 Recently, single passage measurement methods have been reported that use bimodal cantilever excitation suitable for operation in air 5 and in vacuum. 2 They rely on the ability to separate magnetic from non-magnetic (van der Waals or electrostatic) forces on the basis of their different decay lengths.…”
mentioning
confidence: 99%
“…There the feedback parameter is the amplitude of the cantilever oscillation. Bimodal AFM operation is compatible with the presence of a variety of interaction forces such as mechanical [10,24], electrostatic [21], or magnetic [25]. Kawai et al have demonstrated that bimodal excitation and detection are compatible with frequency modulation AFM operation in an ultrahigh vacuum [26,27].…”
mentioning
confidence: 99%